Determination of co-sensitization is an important step in improving the effectiveness of allergen-specific immunotherapy in patients with pollen disease - Dityatkovska , E.M.; Biletska , S.V. (Medicni Perspektivi, 2022)
In order to increase the effectiveness of allergen-specific immunotherapy in patients with pollen disease, the profile of allergen sensitization was determined at the molecular level, performed in 47 patients with clinical manifestations of seasonal rhinoconjunctivitis and perennial allergic rhinitis during a long time period. Allergic examination of patients included history taking, molecular blood tests using ALEX technology to determine the level of specific antibodies class lgE of major and minor components of pollen and household allergens and diagnostic skin tests (pre-test). Assessment of the main clinical manifestations of allergic rhinitis was performed according to the recommendations of the European Association of Allergists and Immunologists. The severity of nasal symptoms was determined by the TNSS scale, and ocular symptoms - by the TOSS scale. Integral assessment of the intensity of clinical symptoms of allergic rhinitis was calculated as the sum of scores by the main symptoms. According to the results of molecular allergy diagnostics, the profile of allergic sensitization in patients with pollen disease was determined, which established the presence of specific lgE - antibodies to major allergy components of ragweed pollen (nAmb a1) – in 91.5±4.1% of patients, wormwood (nArt v3, nArt v1) – in 40.4±7.2%, meadow thyme (rPh1 p1, rPh1 p5b) – in 17.0±5.5%, house dust mites (Der p1, Der p2) – in 29.8±6,7%. Developed on the basis of molecular allergy diagnostics, the profile of allergological sensitization to allergocomponents allows to obtain complete and detailed information on patient sensitization (diagnose a real allergy), cross-reactivity to other allergens, justify the feasibility and predict the effectiveness of allergen-specific immunotherapy.